Home advantage and the debate about competitive balance in professional sports leagues - Forrest, D.; Beaumont, J.; Goddard, J.; Simmons, R. (Journal of Sports Sciences, 2005)
A recurrent theme in sports economics is the extent to which overall league attendances will be raised by measures, such as revenue sharing, which aim to improve competitive balance. This debate has ignored the phenomenon of home advantage, which may, however, be important to the extent that, if all teams had equal talent, all matches may then be weighted heavily in favour of the home team. We present an analysis of the relationship between attendance and match-level uncertainty in the English Football League. A simulation from our model indicates that equality of playing talent would in fact lower aggregate attendance. This result is explained by the loss of prospectively the most uncertain games, where weak teams have home advantage over strong teams.